PENGEMBANGAN MODEL PEMBELAJARAN BAHASA ARAB BERBANTUAN MULTIMEDIA KOMPUTER - Prihartini, Yogia (Jurnal Al-Ashlah, 2017)
English : This research and development result in a learning model that could be used to improve oral communication that was divided into five different learning phase, which is, orientation phase, ordering command phase, role exchange phase, structured practice phase, and guided practice phase. It could also improve oneâs understanding of Arabic grammar/qawaid (nahwuwasharfi) which consist of elements in Arabic language that consist of Letters (harf), Words (kalimatu), Sentences (jumlatu), sibhuljumlah and articles (uslub) and fit into Arabic grammar.The result of this study implies that development result study model emphasize in college studentsâ activities in their learning process. The learning process done by the lecturers using Arabic language as the language of instruction started by the pronunciation of the vocabularies and itâs demonstration without translating it into Bahasa Indonesia. After they were capable of demonstrating the acquired vocabularies, college students trained in reproducing the language orally using question and answer activities, whether structurally, or guided.The study results showed that the quality of this multimedia teaching of Arabic language fall into the âfineâ category, acquiring average score of 43.92 and ideal percentage of 87.85%. Based on the test results, it can be concluded that the developed Arabic language multimedia learning is fit to be used as a source of learning by college students and accompanying media for lecturers in teaching process.Keywords: Development, arabic language learning model,computer multimediaÂ Indonesia:Penelitian dan pengembangan ini menghasilkan model pembelajaran yang dapat meningkatkan kemampuan komunikasi lisan yang terdiri atas lima fase pembelajaran, yaitu, fase orientasi, fase pemberian perintah, fase bertukar peran, fase latihan terstruktur (structured practice), dan fase latihan terbimbing (guided practice).serta dapat meningkatkan pemahaman terhadap tatabahasa arab/ qawaid(nahwu wa sharfi ) yang terdiri dari unsur-unsur bahasa Arab yang terdiri dari Huruf (harf), Kata (kalimatu), kalimat (jumlatu), sibhul jumlah dan wacana (uslub) serta sesuai dengan kaidah-kaidah bahasa Arab.Hasil penelitian ini memberikan implikasi antara lain model pembelajaran hasil pengembangan menekankan aktivitas mahasiswa dalam proses pembelajaran. Pembelajaran yang dilakukan dosen dengan menggunakan bahasa Arab sebagai bahasa pengantar ini dimulai dengan menyebutkan kosa kata dan mendemonstrasikannya tanpa menerjemahkan kedalam bahasa Indonesia dan meminta mahasiswa mendemostrasikannya. Setelah mampu mendemostrasikan kosa kata yang dipelajari, mahasiswa berlatih memproduksi bahasa lisan melalui kegiatan tanya jawab baik secara terstruktur maupun secara terbimbing.Hasil penelitian menunjukkan bahwa kualitas pengembangan multimedia pembelajaran bahasa Arab ini dalam kategori sangat baik dengan memperoleh skor rata-rata 43,92 dengan presentase keidealan sebesar 87,85%. Berdasarkan pengujian yang telah dilakukan, maka dapat disimpulkan bahwa multimedia pembelajaran bahasa Arab yang dikembangkan layak untuk dipergunakan sebagai salah satu sumber belajar mahasiswa dan sebagai media pendamping bagi pengajar dalam proses pembelajaran.Kata Kunci: Pengembangan, Model Pembelajaran Bahasa Arab, Multimedia Komputer